2013
DOI: 10.1016/j.healthplace.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Work stress: Its components and its association with self-reported health outcomes in a garment factory in Bangladesh—Findings from a cross-sectional study

Abstract: Bangladesh is one of the leading exporters of ready-made garments (RMG) worldwide producing at very low cost almost exclusively for Western markets. Empirical evidence on psychologically adverse working conditions and their association with health in the RMG setting remains sparse. Drawing on insights from previous ethnographic research, we conducted a cross-sectional epidemiological study among 332 RMG workers in Dhaka, Bangladesh. High work-related demands and poor interpersonal resources represented key com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
43
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 26 publications
10
43
2
Order By: Relevance
“…In the process of coping with this imbalance, the level of stress among employees increased (Esson, 2004) resulting in depression, strain, and anxiety (Sharma & Dhar, 2015) indicating lower psychological health. It was also found that stressed employees were less active and attentive in accomplishing the tasks and showed signs of nervousness (Steinisch et al, 2013). Thus, stress was found to have an inverse relationship with psychological health (Tyagi & Lochan Dhar, 2014).…”
Section: Mediating Role Of Stressmentioning
confidence: 97%
“…In the process of coping with this imbalance, the level of stress among employees increased (Esson, 2004) resulting in depression, strain, and anxiety (Sharma & Dhar, 2015) indicating lower psychological health. It was also found that stressed employees were less active and attentive in accomplishing the tasks and showed signs of nervousness (Steinisch et al, 2013). Thus, stress was found to have an inverse relationship with psychological health (Tyagi & Lochan Dhar, 2014).…”
Section: Mediating Role Of Stressmentioning
confidence: 97%
“…These factors appear to have made wages and working conditions more favourable compared to the past. workers of a garment factory based in the capital city of Dhaka (Steinisch et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…We asked the respondents whether they had been absent from work due to illness in the previous year. We used the shortened version of the ERIM questionnaire that had previously been used for analysing the health outcomes of RMG workers (Dragano et al, 2010;Steinisch et al, 2013). In line with the previous studies, we measured efforts based on Reward was measured using five aspects: social support, salary, recognition, promotion prospects and job security.…”
Section: Dependent Variablementioning
confidence: 99%
“…2,6,7 The mechanism of how occupational stress may affect workers' health has been broadly explained by two most popular mechanisms as per the cotemporary stress theories. [8][9][10] First, occupational stress can affect the psychological responses (autonomic, neuroendocrine and immune) by directly influencing the organism's main stress axes thereby increasing the host vulnerability and resistance or directly stimulating to the disease mechanisms. The second mechanism hints at an indirect pathway functioning in the form of behavioural patterns and habits of people under work stress which Apart from this, individual traits may also influence the interaction between stressors and strain of which a feature called negative affectivity (NA) has been drawing lot of researchers attention.…”
Section: Introductionmentioning
confidence: 99%